Rethinking collection development and management - Albitz, Becky; Avery, Christine, 1954-; Zabel, Diane, 1957- (Libraries Unlimited, 2014)
"This collection of thought-provoking essays by visionary and innovative library practitioners covers theory, research, and best practices in collection development, examining how it has evolved, identifying how some librarians are creatively responding to these changes, and predicting what is coming next"--Resumé vydavatele